Report on practice in industry training in fish culture - Manga, Augusto O. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1959)
As we know, fishing is the third industry in the Philippines and it is one of the best sources of our government revenue. Wider studies in fishing should be undertaken thoroughly by each and every citizen of our country. In connection with these studies and demonstration centers are being opened by the government, so that eager citizens could study and learn theoretically and practically the modern methods of culturing, catching and preserving fish. The author wishes to express his sincerest thanks to the outstanding fishpond operators in the province of Ctanduanes; Messrs. Juan P. Siatong, Sofio Alcantara (fish culture graduate), Leonardo Magat, Paulion Rodolfo, and Esteban Vallejos (former chief of irrigation system in Ctanduanes) in helping him during the four-months training. Furthermore he is a greatly indebted to Prof. Alfonso R. Sebastian (head, department of inland fisheries), Mr. Marcelino N. Sabando, Mrs. Medina N. Delmendo, Prof. Nasarion AS. Pidinaoan (director, college of fisheries), Mr. praciliano Corpuz (junior apperaiser of the DBP and to all his instructors in the college of fisheries. Without them this book will not be successful.
Keywords: Fish-culture.